Perlindungan Hukum Pencurian Data Pribadi dan Bahaya Penggunaan Aplikasi Pinjaman Online - Rizki Akbar Maulana; Rani Apriani (Fakultas Hukum Universitas Djuanda Bogor, 2021)
Advances in technology and information in Indonesia make it easy for the community because it makes it easier to carry out various activities quickly and accurately. However, from the advantages of technology and information, there are shortcomings that arise, namely economic crimes in protecting customers' personal data. The research method used is juridical normative with a descriptive approach and uses primary and secondary legal materials. The results of the discussion concluded that the current legal protection related to personal data in Indonesia has not been specifically and comprehensively regulated due to regulations regarding personal data which are still general in nature. As a result of the absence of these special rules, it can lead to legal uncertainty which makes people confused about the legal protection provided by the state for their personal data. Then the actions that need to be taken by the customer regarding the occurrence of data leakage can be done in two ways of complaint, namely verbally or in writing. If in the complaint problem there is no good faith on the part of the bank itself, the problem can be submitted and resolved through the court.